Reduced quality of life and greater psychological distress in vasovagal syncope patients compared to healthy individuals. Issue 2 (10th December 2018) - Ng, Jessica; Sheldon, Robert S.; Ritchie, Debbie; Raj, Vidya; Raj, Satish R.
Abstract: Background: Vasovagal syncope (VVS) patients have a reduced health‐related quality of life (HRQoL). There are limited data comparing HRQoL and psychological profile in VVS patients and healthy individuals. We tested the hypothesis that VVS patients have greater impairment in both HRQoL and psychological profile compared to healthy nonfainting individuals, and that both outcome measures are negatively correlated for VVS patients. Methods: The RAND 36‐Item Health Survey (RAND36), global health visual analogue scale (VAS), Hospital Anxiety and Depression Scale, Anxiety Sensitivity Index, and Positive and Negative Affect Schedule – Expanded Form were completed by healthy individuals and at baseline by VVS patients enrolled in the Second Prevention of Syncope Trial, a randomized, placebo‐controlled trial of fludrocortisone for VVS. Results: Data were available on 76 VVS patients (34 ± 14 years; 68% F) and 85 healthy participants (35 ± 11 years; 80% F). Compared to healthy participants, VVS patients reported poorer HRQoL on all scales of the RAND36 and the VAS. VVS patients had significantly greater anxiety, depression, and anxiety sensitivity (each P < 0.001). VVS patients had more negative affect (P < 0.001) and less positive affect (P = 0.003) compared to healthy participants. Anxiety, depression, and anxiety sensitivity were negatively correlated with HRQoL for VVS patients, but not for healthy participants. Conclusion: In this first direct comparison, VVS patients have a significantly reduced HRQoL and more anxiety and depression compared to healthy nonfainting individuals. For VVS patients, there is a relationship between psychological distress and HRQoL, suggesting a potential benefit from more comprehensive assessment and treatment.